IMPLEMENTASI KURIKULUM 2013 DALAM PROSES PEMBELAJARAN SENI RUPA DI SMP NEGERI BATUSANGKAR - Restu Yulia Suhanta, Dra. Zubaidah, M.Pd., Drs. Wisdiarman, M.Pd. (Serupa The Journal of Art Education, 2018)
This study aims to get know the implementation of 2013 curriculum in art lesson each of state junior high school in Batusangkar city. This research is qualitative with deductive approuch. The data get through interview for getting the information about planning, strategy, evaluation of learning, observation of the application of learning, and documentation like RPP. Yhe informant is the art teacher in each school. Result of this research is lesson planning is not suitable yet with the RPP, the lesson strategy not in accordance with the scientific approach, and lesson evaluation not going like the concept of scientific approach, and lesson evaluation not going like the concept of scientific valuation.Keywords: implementation of 2013 curriculum